PENGUATAN KOMPETENSI GURU SEKOLAH DASAR MELALUI IMPLEMENTASI PROYEK BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT - Sofiyana, Marinda Sari; Suyitno; Lukma, Hazairin Nikmatul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2025)
Elementary education plays a crucial role in developing 21st-century competencies and sustainability awareness from an early age. However, the implementation of project-based learning integrated with Education for Sustainable Development (ESD) remains limited due to teachers’ insufficient understanding and skills in designing contextual learning materials. This community service program aimed to enhance elementary school teachers’ pedagogical competence in developing and implementing ESD-oriented Project-Based Learning (PjBL) modules. The program was conducted at SD Negeri Gembongan, Blitar Regency, involving 12 teachers through an integrated training and participatory mentoring approach. The activities included needs assessment, conceptual strengthening of ESD and PjBL, mentoring in project-based module development, and classroom implementation. Program evaluation employed a mixed-methods approach using pre-tests and post-tests, classroom observation, and teacher response questionnaires. The results indicated a significant improvement in teachers’ understanding of ESD, PjBL, and deep learning concepts. The quality of the developed learning modules improved across all aspects, particularly in the clarity of ESD-oriented learning objectives, coherence of project stages, and utilization of local environmental potential. Classroom implementation demonstrated a very high level of project-based learning execution with active student engagement. Overall, this program contributes to the promotion of more contextual, meaningful, and sustainability-oriented learning practices in elementary schools.